2017
DOI: 10.1021/acs.jpca.7b01223
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer in Mixed Clusters of Methanesulfonic Acid, Methylamine, and Oxalic Acid: Implications for Atmospheric Particle Formation

Abstract: Understanding the properties of atmospheric particles made of several components is a very challenging problem. In this paper, we perform quantum chemical calculations for small multicomponent clusters of atmospheric relevance that incorporate methanesulfonic acid (MSA), methylamine (MA), oxalic acid (OxA), and water (HO). Potential correlations between theoretical predictions of proton transfer in the small clusters and findings of recent experiments on formation of particles of detectable sizes (>2 nm) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 111 publications
(153 reference statements)
1
53
0
Order By: Relevance
“…1. Consistent with previous studies, 57,66 the most stable structure of MSA-MA is an ion pair [H 3 CSO 3 ] À [H 3 NCH 3 ] + , where MSA transfers one proton to MA. In our previous study, we found proton transfer in the small cluster qualitatively correlates particle formation observed experimentally.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…1. Consistent with previous studies, 57,66 the most stable structure of MSA-MA is an ion pair [H 3 CSO 3 ] À [H 3 NCH 3 ] + , where MSA transfers one proton to MA. In our previous study, we found proton transfer in the small cluster qualitatively correlates particle formation observed experimentally.…”
Section: Resultssupporting
confidence: 89%
“…3.1 The 1 : 1 MSA-MA cluster MSA-MA, the smallest cluster, has been studied theoretically. 57,66 The geometries, bond lengths of hydrogen bonds and partial charges on MSA-MA computed at the level of PBE/cc-pVDZ are shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1993), is the water-soluble organic acid, so it has high concentration in aerosols (Kawamura et al, 2013;van Pinxteren et al, 2014;Deshmukh et al, 2016;Wang et al, 2016). In addition to accumulating in aerosols, oxalic acid, as an organic acid in the gas phase, has been found to enhance the new particle formation (NPF) (Xu et al, 2010;Weber et al, 2012;Xu and Zhang, 2012;Weber et al, 2014;Peng et al, 2015;Miao et al, 2015;Zhao et al, 2016;Chen et al, 2017;Xu et al, 2017;Arquero et al, 2017;Zhang, 2010). Theoretical studies about the effect of oxalic acid on atmospheric particle nucleation and growth have 5…”
Section: Introductionmentioning
confidence: 99%
“…shown that it can form stable complexes with water (Weber et al, 2012), sulfuric acid (Xu et al, 2010;Xu and Zhang, 2012;Miao et al, 2015;Zhao et al, 2016), ammonia (Weber et al, 2014;Peng et al, 2015) and amines (Chen et al, 2017;Xu et al, 2017;Arquero et al, 2017) via intermolecular hydrogen bond. The potential of oxalic acid for contributing to the NPF is mainly attributed to its capability of forming hydrogen bond with hydroxyl and/or carbonyl-type functional group.…”
Section: Introductionmentioning
confidence: 99%